Impact of low-dose CT screening for lung cancer on ethnic health inequities in New Zealand: a cost-effectiveness analysis - Sue Crengle; Giorgi Kvizhinadze; Melissa McLeod; Peter Sandiford; Karen Bartholomew (BMJ Open)
Objective There are large inequities in the lung cancer burden for the Indigenous Māori population of New Zealand. We model the potential lifetime health gains, equity impacts and cost-effectiveness of a national low-dose CT (LDCT) screening programme for lung cancer in smokers aged 55–74 years with a 30 pack-year history, and for formers smokers who have quit within the last 15 years.Design A Markov macrosimulation model estimated: health benefits (health-adjusted life-years (HALYs)), costs and cost-effectiveness of biennial LDCT screening. Input parameters came from literature and NZ-linked health datasets.Setting New Zealand.Participants Population aged 55–74 years in 2011.Interventions Biennial LDCT screening for lung cancer compared with usual care.Outcome measures Incremental cost-effectiveness ratios were calculated using the average difference in costs and HALYs between the screened and the unscreened populations. Equity analyses included substituting non-Māori values for Māori values of background morbidity, mortality and stage-specific survival. Changes in inequities in lung cancer survival and ‘health-adjusted life expectancy’ (HALE) were measured.Results LDCT screening in NZ is likely to be cost-effective for the total population: NZ$34 400 per HALY gained (95% uncertainty interval NZ$27 500 to NZ$42 900) and for Māori separately (using a threshold of gross domestic product per capita NZ$45 000). Health gains per capita for Māori females were twice that for non-Māori females and 25% greater for Māori males compared with non-Māori males. LDCT screening will narrow absolute inequities in HALE and lung cancer mortality for Māori, but will slightly increase relative inequities in mortality from lung cancer (compared with non-Māori) due to differential stage-specific survival.Conclusion A national biennial LDCT lung cancer screening programme in New Zealand is likely to be cost-effective, will improve total population health and reduce health inequities for Māori. Attention must be paid to addressing ethnic inequities in stage-specific lung cancer survival.